Adult Contractures in Burn Injury: A Burn Model System National Database Study. Issue 1 (January 2017) - Goverman, Jeremy; Mathews, Katie; Goldstein, Richard; Holavanahalli, Radha; Kowalske, Karen; Esselman, Peter; Gibran, Nicole; Suman, Oscar; Herndon, David; Ryan, Colleen M.; Schneider, Jeffrey C.
Abstract : As the overall survival rate for burn injury has improved, increased emphasis is placed on postburn morbidity and the optimization of functional and cosmetic outcomes. One major cause of morbidity and functional deficits is that of joint contractures. The true incidence of postburn contractures and their associated risk factors remains unknown. This study examines the incidence and severity of contractures in a large, multicenter, burn population. The associated risk factors for the development of contractures are determined. Data from the National Institute on Disability and Rehabilitation Research Burn Model System database, for adult burn survivors from 1994 to 2003, were analyzed. Demographic and medical data were collected on each subject. The primary outcome measures included the presence of contractures, number of contractures per patient, and severity of contractures at each of nine locations (shoulder, elbow, hip, knee, ankle, wrist, neck, lumbar spine, and thoracic spine) at time of hospital discharge. Regression analysis was performed to determine predictors of the presence, severity, and numbers of contractures, with P < .05 used for statistical significance. Of the 1865 study patients, 620 (33%) developed at least 1 contracture at hospital discharge. Among those with at least one contracture, the mean is three (3.38) contractures per person. The shoulder was the most frequently contracted joint (23.0%), followed by the elbow (19.9%), wrist (17.3%), ankle (13.6%), and knee (13.4%). Most contractures were mild (47.2%) or moderate (32.9%) in severity. Statistically significant predictors of contracture development were male sex, black race, Hispanic ethnicity, medical problems, neuropathy, TBSA grafted, and TBSA burned. Predictors of the severity of contracture included male sex, black race, medical problems, neuropathy, TBSA grafted, and TBSA burned. Predictors of the number of contractures included male sex, medical problems, flash burn, neuropathy, TBSA burned, and TBSA grafted. Similar to a previous single-center study on postburn contractures, approximately one third of the patients with an eligible burn injury requiring autografting developed a contracture at hospital discharge. It is likely that these contractures develop despite early therapeutic interventions such as positioning and splinting; therefore, the challenge to the burn community remains, to identify new and better prevention strategies. Abstract : Supplemental Digital Content is available in the text.